1956
DOI: 10.1002/hlca.19560390725
|View full text |Cite
|
Sign up to set email alerts
|

Über die Bildung von 5‐Formylbrenzschleimsäure aus D‐Galakturonsäure

Abstract: 5‐Carboxy‐2‐furfural is formed in a few minutes by the action of cone. sulfuric acid on D‐galacturonic acid. This substance seems to be mainly responsible for Dische's colour reaction of hexuronic acids with sulfuric acid and carbazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1958
1958
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Decarboxylation of d -galacturonic acid to l -arabinose as the first step of reaction followed by dehydration and cyclization yielding typical degradation products of pentoses has been assumed as the main degradation pathway . Stutz and Deuel found out that only small amounts of l -arabinose are formed during thermal treatment of d -galacturonic acid and that there have to be other and more important degradation pathways . Our studies also revealed that decarboxylation is not the only degradation pathway leading to the known degradation products because of their imbalanced concentrations in model studies of l -arabinose and d -galacturonic acid under the same reaction conditions.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Decarboxylation of d -galacturonic acid to l -arabinose as the first step of reaction followed by dehydration and cyclization yielding typical degradation products of pentoses has been assumed as the main degradation pathway . Stutz and Deuel found out that only small amounts of l -arabinose are formed during thermal treatment of d -galacturonic acid and that there have to be other and more important degradation pathways . Our studies also revealed that decarboxylation is not the only degradation pathway leading to the known degradation products because of their imbalanced concentrations in model studies of l -arabinose and d -galacturonic acid under the same reaction conditions.…”
Section: Introductionmentioning
confidence: 57%
“…4 Stutz and Deuel found out that only small amounts of L-arabinose are formed during thermal treatment of D-galacturonic acid and that there have to be other and more important degradation pathways. 9 Our studies also revealed that decarboxylation is not the only degradation pathway leading to the known degradation products because of their imbalanced concentrations in model studies of L-arabinose and D-galacturonic acid under the same reaction conditions.…”
Section: ■ Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The absorbance spectra of the pigment formed by corn sirup dextrins, alone and in presence of pectin, are shown in Figure 2. This shows that the maxi- mum for pectin is 532 m/t-McComb and McCready (18) reported a maximum of 525, Dische (7) and Stutz (22,23), 527-while that for dextrin is 542 mg. Holzman, MacAllister, and Neimann (15) and others have reported values near 545 mgt for hexoses. Pectins show a secondary maximum at 405 mg, but this is lower, and shifted to 415 mg in the case of dextrin.…”
Section: Recovery Of Pectin By Carbazole Assay On Alcoholmentioning
confidence: 79%